Enhanced Photocatalytic Activity of a Molybdate‐Intercalated Iron‐Based Layered Double Hydroxide. Issue 3 (24th January 2017) - Mohapatra, Lagnamayee; Patra, Dhananjaya; Parida, Kulamani; Zaidi, Syed Javaid
Abstract : Herein, we report the design and successful fabrication of new Mg/Fe layered double hydroxides (LDHs) with different Mg/Fe molar ratios (2:1, 3:1, and 4:1) by a coprecipitation method. The prepared Mg/Fe (4:1) LDH sample with high crystallinity and phase purity was further modified by intercalation with molybdate anions. The structural, morphological, optical, electrochemical, and photocatalytic properties of the prepared catalysts were subsequently examined. In comparison with that of the Mg/Fe (4:1) LDH, the photocatalytic activity of the Mg/Fe (4:1) material with molybdate anions intercalated in the interlayer for the degradation of methyl orange (MO) was enhanced, and the processed followed apparent first‐order kinetics. Radical‐trapping experiments demonstrated that h +, OH · radicals, and O2 –· radicals are the dominant reactive species for pollutant degradation. The highest photocatalytic activity of molybdate‐intercalated LDH is attributed mainly to the combined effects of its layered structure with Mg II –O–Fe III linkages and intercalated molybdate anions, which act as visible‐light absorption centers towards higher wavelengths and can promote charge‐carrier trapping as well as hinder the photogenerated electron–hole recombination. The time‐resolved photoluminescence (TRPL) spectra demonstrated the prolonged charge separation under visible light. Abstract : The modification of Mg/Fe layered double hydroxides through intercalation with molybdate anions produces photocatalysts with excellent activities for the degradation of methyl orange. The observed superior photocatalytic activity is mainly attributed to a large band gap, prolonged lifetime, and faster interfacial charge‐transfer rate.